The evolutionary origins of the southern ocean Philobryid bivalves: hidden biodiversity, ancient persistence. - Jennifer A Jackson; Katrin Linse; Rowan Whittle; Huw J Griffiths (PLoS ONE, 2015)
Philobryids (Bivalvia: Arcoida) are one of the most speciose marine bivalve families in the Southern Ocean and are common throughout the Southern Hemisphere. Considering this diversity and their brooding reproductive mode (limiting long-distance dispersal), this family may have been present in the Southern Ocean since its inception. However Philobrya and Adacnarca appear only in the Quaternary fossil record of the Antarctic, suggesting a much more recent incursion. Molecular dating provides an independent means of measuring the time of origin and radiation of this poorly known group. Here we present the first combined molecular and morphological investigation of the Philobryidae in the Southern Ocean. Two nuclear loci (18S and 28S) were amplified from 35 Southern Ocean Adacnarca and Philobrya specimens, with a combined sequence length of 2,282 base pairs (bp). Adacnarca specimens (A. nitens and A. limopsoides) were resolved as a strongly supported monophyletic group. Genus Philobrya fell into two strongly supported groups ('sublaevis' and 'magellanica/wandelensis'), paraphyletic with Adacnarca. The A. nitens species complex is identified as at least seven morpho-species through morphological and genetic analysis of taxon clustering. Phylogenetic analyses resolve Philobryidae as a strongly supported monophyletic clade and sister taxon to the Limopsidae, as anticipated by their classification into the superfamily Limopsoidea. Bayesian relaxed clock analyses of divergence times suggest that genus Adacnarca radiated in the Southern Ocean from the Early Paleogene, while P. sublaevis and P. wandelensis clades radiated in the late Miocene, following the formation of the Antarctic Circumpolar Current.